2021
DOI: 10.3390/s22010102
|View full text |Cite
|
Sign up to set email alerts
|

A Wearable Biofeedback Device to Increase Gait Swing Time Could Have Positive Effects on Gait among Older Adults

Abstract: Older adults walk with a shorter stride length, reduced hip range of motion (ROM) and higher cadence. These are signs of reductions in walking ability. This study investigated whether using a wireless smart insole system that monitored and provided biofeedback to encourage an extension of swing time could increase stride length and hip flexion, while reducing the cadence. Seven older adults were tested in this study, with and without the biofeedback device, in an outdoor environment. Gait analysis was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…This raises the question of how best to apply goal-oriented paradigms (which was suggested by the therapists) without overloading the feedback stimulus with information. One option could be to drop the plain wading sound in these cases so that the patient can focus exclusively on the positive or negative feedback stimuli, similar to designs from past studies [25,70].…”
Section: Feedback Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the question of how best to apply goal-oriented paradigms (which was suggested by the therapists) without overloading the feedback stimulus with information. One option could be to drop the plain wading sound in these cases so that the patient can focus exclusively on the positive or negative feedback stimuli, similar to designs from past studies [25,70].…”
Section: Feedback Designmentioning
confidence: 99%
“…A good example is by Rodger et al [24], who sonified instantaneous limb swing velocity in Parkinson's disease patients as musical pitch variations, finding that it led to, as hypothesized, a significant reduction in step length variability. Giraldo-Pedroza et al [25] found that threshold-based haptic feedback on swing time was able to induce significant changes in stride length, swing time, and hip flexion in healthy older adults (who typically take short steps with a reduced hip motion range). Hemiparetic patients can exhibit considerable swing phase asymmetry due to reduced joint motion ranges and compensatory strategies (e.g., circumduction) prevalent on the most-affected side [1].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it makes it possible to perform actions that control the behavior of this variable [ 26 ]. An example of this is shown in conventional medicine in patients with joint and muscle pain problems [ 34 , 35 , 36 ], where biofeedback techniques generate self-correction of body positions that benefit study subjects.…”
Section: Related Workmentioning
confidence: 99%
“…Recent literature has shown that information- and communication-technology (ICT)-based solutions can be a suitable way to promote health among older adults [ 3 , 5 , 6 ], with special attention paid to those who are living in a rural context [ 5 ]. It has been observed that the use of wearable and environmental devices, in combination with appropriate activities, applications, and feedback [ 7 ], can improve the promotion of healthy habits [ 8 , 9 ]. Moreover, the caregiving relationship is crucial in promoting the health and well-being of older adults [ 10 ].…”
Section: Introductionmentioning
confidence: 99%